Effectiveness of Jigsaw Type Cooperative Learning Method to Increase Motivation and Learning Outcomes of Pancasila Class X Students IPS High School 1 Meukek South Aceh District - Rasima; Yasni, Hilma; Rahmi, Cut; Lizam, T. Cut; Orisinal; Julissasman; Susanti (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study examines the effectiveness of the jigsaw-type cooperative learning method to increase the motivation and learning outcomes of sociology students in class X IPS SMA N1 Meukek, South Aceh Regency. This research is quantitative and experimental. The sample was class X with two learning models, one treatment and one control. Researchers used observation methods, questionnaires, and analyzed statistics in SPSS for Windows 23. The results showed that the learning motivation and learning outcomes of students in the experimental class using the jigsaw cooperative learning model It can be seen that student learning motivation in the experimental class increased from the category of often to always, with the highest score of 85 and an average score of 51.4%. While the learning outcomes of experimental class students were effectively used in improving student learning outcomes in sociology subjects, with the highest pretest score of 86 with an average of 66.7994 and the highest post-test score of 86 with an average of 80.9854, which means that the use of the jigsaw-type cooperative learning model in increasing student motivation and learning outcomes is very effective.